Pengaruh Pengetahuan Perpajakan, Ketegasan Sanksi Pajak, dan Kualitas Pelayanan terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kabupaten Cilacap - Yoiz Shofwa Shafrani (Mabsya: Jurnal Manajemen Bisnis Syariah, 2019)
Dealing with taxation in Cilacap Regency, an MoU was conducted between Cilacap Regional Police and the Regional Revenue Service Unit or Samsat Cilacap. The signing was to help the government raise awareness of paying taxes for motor vehicle owners. The purpose of this study is to determine the effect of taxation, tax sanction assertiveness, and service quality on motor vehicle taxpayer decisions in Cilacap district. The results of this study that tax knowledge has no effect on taxpayer compliance. Firmness of tax sanctions does not affect taxpayer compliance. Beer service quality has an effect on tax compliance. Knowledge of taxation, the firmness of tax sanctions and the quality of service together affect the taxpayer compliance.